Sequential activation of classic PKC and estrogen receptor α is involved in estradiol 17ß-D-glucuronide-induced cholestasis. - Ismael R Barosso; Andrés E Zucchetti; Andrea C Boaglio; M Cecilia Larocca; Diego R Taborda; Marcelo G Luquita; Marcelo G Roma; Fernando A Crocenzi; Enrique J Sánchez Pozzi (PLoS ONE, 2012)
Unlabelled Estradiol 17ß-D-glucuronide (E17G) induces acute cholestasis in rat with endocytic internalization of the canalicular transporters bile salt export pump (Abcb11) and multidrug resistance-associated protein 2 (Abcc2). Classical protein kinase C (cPKC) and PI3K pathways play complementary roles in E17G cholestasis. Since non-conjugated estradiol is capable of activating these pathways via estrogen receptor alpha (ERα), we assessed the participation of this receptor in the cholestatic manifestations of estradiol glucuronidated-metabolite E17G in perfused rat liver (PRL) and in isolated rat hepatocyte couplets (IRHC). In both models, E17G activated ERα. In PRL, E17G maximally decreased bile flow, and the excretions of dinitrophenyl-glutathione, and taurocholate (Abcc2 and Abcb11 substrates, respectively) by 60% approximately; preadministration of ICI 182,780 (ICI, ERα inhibitor) almost totally prevented these decreases. In IRHC, E17G decreased the canalicular vacuolar accumulation of cholyl-glycylamido-fluorescein (Abcb11 substrate) with an IC50 of 91±1 µM. ICI increased the IC50 to 184±1 µM, and similarly prevented the decrease in the canalicular vacuolar accumulation of the Abcc2 substrate, glutathione-methylfluorescein. ICI also completely prevented E17G-induced delocalization of Abcb11 and Abcc2 from the canalicular membrane, both in PRL and IRHC. The role of ERα in canalicular transporter internalization induced by E17G was confirmed in ERα-knocked-down hepatocytes cultured in collagen sandwich. In IRHC, the protection of ICI was additive to that produced by PI3K inhibitor wortmannin but not with that produced by cPKC inhibitor Gö6976, suggesting that ERα shared the signaling pathway of cPKC but not that of PI3K. Further analysis of ERα and cPKC activations induced by E17G, demonstrated that ICI did not affect cPKC activation whereas Gö6976 prevented that of ERα, indicating that cPKC activation precedes that of ERα. Conclusion ERα is involved in the biliary secretory failure induced by E17G and its activation follows that of cPKC.